11-(x+3)=

Simple and best practice solution for 11-(x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-(x+3)= equation:


Simplifying
11 + -1(x + 3) = 0

Reorder the terms:
11 + -1(3 + x) = 0
11 + (3 * -1 + x * -1) = 0
11 + (-3 + -1x) = 0

Combine like terms: 11 + -3 = 8
8 + -1x = 0

Solving
8 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -1x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -1x = 0 + -8
-1x = 0 + -8

Combine like terms: 0 + -8 = -8
-1x = -8

Divide each side by '-1'.
x = 8

Simplifying
x = 8

See similar equations:

| 300(14-x)+800x=6.200 | | -5(r+2)=-81 | | 4(x+2)+6= | | 12-5*x=-33 | | -11.6h+11.55=-12.7h | | -9.1c+19.02=-14.3c+11.74 | | 21x-8=5(4x+5)-17 | | -5(r+2)=81 | | -1/2q-4=9 | | 20+4y=40 | | 5(10-2n)=70 | | 8(x+15)=7 | | 1/5q-49 | | 6(2g-1)=13 | | 4(g+4)=2(4-g) | | 4x+4=7y | | 4y+4=7y | | 1/3x10=55 | | -4(3x-7)=-12x-28 | | 5x+15=3(x+5) | | 112x=245x+95 | | 5.5=7.9-0.6x | | x-41=70 | | 7=-x+264 | | y+51=89 | | -37-8= | | h(t)=-16t^2+20t+17 | | x(x+3)-5=3x+20 | | 3x+7-5(x+1)=2x+5 | | 5y+3y-5=6(4y+3) | | -4s+9=-24 | | 2r+4=-16 |

Equations solver categories